An Analysis of Hospital Information Systems and Service Quality on Patient Satisfaction in Maternal and Child Health Services in Indonesia - Nurmalia Lusida; Andriyani Andriyani; Irna Hasanah; Raghib Filhaq; Atthariq Atthariq (Eastasouth Institute, 2026)
This study analyzes the effect of Hospital Information Systems (HIS) and service quality on patient satisfaction in maternal and child health care services in Indonesia. A quantitative research design was applied using a cross-sectional approach involving 150 respondents who had utilized maternal and child health services. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using SPSS version 25. The analysis included descriptive statistics, validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that both Hospital Information Systems and service quality have a positive and significant effect on patient satisfaction. Service quality demonstrates a stronger influence compared to HIS. The coefficient of determination (R²) of 0.610 indicates that 61% of the variation in patient satisfaction is explained by the two independent variables. The findings highlight the importance of integrating digital health systems with high-quality service delivery to improve patient satisfaction in maternal and child health care settings. This study provides practical implications for hospital management and policymakers in strengthening healthcare service performance through technological and human resource improvements.